2016
DOI: 10.1208/s12248-016-9948-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Immunogenicity Risk Due to Host Cell Protein Impurities in Antibody-Based Biotherapeutics

Abstract: A potential risk factor for immunogenicity of a biotherapeutic is the low levels of host cell protein (HCP) impurities that remain in the product following the purification process. During process development, significant attention has been devoted to removing HCPs due to their potential safety risk. Samples from different purification steps of several monoclonal antibodies (mAbs) purified by one type of platform were evaluated for their residual Chinese Hamster Ovary (CHO) cell-derived HCP content. HCPs in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Calculated p ‐values for ANOVA comparisons of each peptide resin compared to both benchmark resins (Capto Q and Capto Adhere) are provided. Species identified by shotgun proteomics in this study identified as “problematic” based on prior art (Aboulaich et al, ; Bailey‐Kellogg et al, ; Chiu et al, ; Fischer et al, ; Gagnon et al, ; Goey et al, ; Jawa et al, ; Levy et al, ; Mechetner et al, ; Zhang et al, ). * p < .05.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Calculated p ‐values for ANOVA comparisons of each peptide resin compared to both benchmark resins (Capto Q and Capto Adhere) are provided. Species identified by shotgun proteomics in this study identified as “problematic” based on prior art (Aboulaich et al, ; Bailey‐Kellogg et al, ; Chiu et al, ; Fischer et al, ; Gagnon et al, ; Goey et al, ; Jawa et al, ; Levy et al, ; Mechetner et al, ; Zhang et al, ). * p < .05.…”
Section: Resultsmentioning
confidence: 82%
“…This study focuses on problematic HCPs in three primary categories based on risk factors described above: (a) HCPs co‐eluting with mAbs in the capture step, herein referred to as Group I (Aboulaich et al, ; Gagnon et al, ; Levy et al, ; Mechetner et al, ; Zhang et al, ), including IgG‐associated and Protein A‐binding HCPs, (b) HCPs that cause product degradation, or Group II (Aboulaich et al, ; Bee et al, ; Chiu et al, ; Goey et al, ; Zhang et al, ), and (c) HCPs with high immunogenicity risk, or Group III (Bailey‐Kellogg et al, ; Fischer et al, ; Goey et al, ; Jawa et al, ). In typical mAb platform processes, the large majority of HCPs are removed at the product capture step with Protein A‐based adsorbents; thus, the design of the subsequent intermediate and final polishing steps is highly dependent on their ability to remove the species that co‐elute with IgG from Protein A.…”
Section: Introductionmentioning
confidence: 99%
“…DNA, RNA, proteins, lipids, and virus) present in the cell factory and cell culture medium (Bracewell, Francis, & Smales, ). The removal of these “process” impurities from the harvest fluid particularly host cell proteins (HCPs), which even at relatively low levels have the potential to elicit an immunogenic response in patients, is considered to be a critical quality attribute during the process development (Jawa et al, ). The second class of impurity encountered during the manufacture arise from molecular variants of the therapeutic protein itself.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, novel fragmentation methods were being developed that allowed extensive characterization of MAbs in the gas phase (4042). Currently, MS plays a central role in the routine quality control of therapeutic-MAb production (4345), and new MS-based methodologies for monitoring are continuously appearing in the literature. The remainder of this review will focus on translating MS-based methods for quantifying therapeutic MAbs into the clinical laboratory with a focus on selecting methods that result in the highest level of analytical sensitivity and specificity with respect to each patient's endogenous Ig repertoire.…”
Section: History Of Mab Measurement By Msmentioning
confidence: 99%